A New Chapter in China's Stance on Labour Protection? An Assessment of the China–EU CAI. (17th August 2022) - Yan, Yueming
ABSTRACT: China overhauled its pre-existing image of being insufficiently friendly to sustainable development in international investment agreements (IIAs) with its sweeping, specific, and strong commitments to labour rights protection in the Comprehensive Agreement on Investment (CAI) recently concluded with the European Union. This article provides an assessment of these labour provisions and examines their impact on China's national, regional, and global stances on labour protection. Firstly, it analyses the features and purposes of different types of labour provision and the integrated mechanism for settling disputes on labour issues. This article then identifies the gap between China's commitments under the CAI and its actual practices and presents a wish list for China to enhance labour protection, including efforts to ratify fundamental International Labour Organization conventions, improve domestic legislation on core labour principles, and enhance corporate social responsibility among Chinese investors. Further, this article assesses the macro-level impacts of these labour provisions. It argues that the CAI presents an opportunity to strengthen sustainable development and labour rights protection within China, along the Belt and Road Initiative, and globally. China is advised to continue incorporating modernized labour standards into its future IIAs.